DEVELOPMENT AND EVALUATION OF IN SITU GELS OF MOXIFLOXACIN FOR THE TREATMENT OF PERIODONTITIS - Hareesh Babu Kunche; Mohammed Gulzar Ahmed; Narayana Charyulu Rompicharla (Indonesian Journal of Pharmacy, 2012)
Gel  dosage  forms  are  successfully  used  as  drug  delivery systems  to  control  drug  release  and  protect  the  medicaments from  a  hostile  environment.  The  main  objective  of  the  present investigation is to formulate and evaluate in situ gels of moxifloxacin  for  the  treatment  of  periodontitis  using  gellan  gum  and sodium  alginate  based  on  the  concept  of  ion  activated  systems. The  system  utilizes  polymers  that  exhibit  sol-to-gel  phase transition due to change in specific physico-chemical parameters. Sol-to-gel transformation occurred in the presence of monovalent/divalent cations. It was found that increase in the concentration of  calcium  ions  produced  stronger  gels.  Formulations  were evaluated for gelling capacity, drug content, clarity, viscosity, gel strength,  spread  ability,  microbiological  studies  and in  vitro release. The results shown by the above characterization studies were  found  to  be  satisfactory.  Experimental  part  showed  that viscosity of  sols  and  gel  strength  was  increased  with  increase  in the concentration of polymers and the sustained release  of drug was observed.  The formulations were therapeutically efficacious, sterile  and  provided  sustained  release  of  the  drug  over  a  period of  time.  These  results  demonstrated  that  the  developed  system is an alternative to conventional drug delivery systems, provides patient compliance and economical.Key  words:  in  situ  gels,  moxifloxacin,  periodontitis,  polymers,  Ion activation.